1991
DOI: 10.1093/ajcn/53.1.32
|View full text |Cite|
|
Sign up to set email alerts
|

Lysozyme, lactoferrin, and secretory immunoglobulin A content in breast milk: influence of duration of lactation, nutrition status, prolactin status, and parity of mother

Abstract: Milk lactoferrin (LF), lysozyme (LZ), and secretory IgA (sIgA) were measured cross-sectionally in 127 Zaïrean mothers, lactating greater than or equal to 18 mo. The 54 urban mothers were of marginal nutrition status [body mass index (BMI) 22.6 +/- 2.6 kg/m2 and albumin 33.1 +/- 4.5 g/L]. The neighboring rural mothers were of significantly (P less than 0.001) poorer nutrition status (BMI 20.5 +/- 2.2 kg/m2 and albumin 27.7 +/- 5.4 g/L). In both urban and rural mothers, as lactation progressed LF decreased by 33… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
83
3
6

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(108 citation statements)
references
References 29 publications
16
83
3
6
Order By: Relevance
“…The molecular weight of the protein band corresponding to DM lactoferrin was about 80.0 kDa. The quantitative determination of DM lactoferrin ( Figure 2A) gave a result of 0.080 ±0.0035 g/L, similar to that found in mare (0.1 g/L),cow (0.02-0.2 g/L), goat (0.06-0.40 g/L), and sheep milk (0.135 g/L) [20,21], but lower when compared with the lactoferrin content in human milk (up to 1.0-6.0 g/L) [22].…”
Section: Characterization Of Donkey Milk Antimicrobial Factors: Lactosupporting
confidence: 75%
“…The molecular weight of the protein band corresponding to DM lactoferrin was about 80.0 kDa. The quantitative determination of DM lactoferrin ( Figure 2A) gave a result of 0.080 ±0.0035 g/L, similar to that found in mare (0.1 g/L),cow (0.02-0.2 g/L), goat (0.06-0.40 g/L), and sheep milk (0.135 g/L) [20,21], but lower when compared with the lactoferrin content in human milk (up to 1.0-6.0 g/L) [22].…”
Section: Characterization Of Donkey Milk Antimicrobial Factors: Lactosupporting
confidence: 75%
“…Recovery studies showed close agreement between the theoretical and measured protein concentrations in dilution-overloadind assays (linear recovery on large ranges of concentrations with mean percentage very close to 100%). Results of the measurements of nine proteins performed together in a great number of human mature milk samples are, for the most part, in good agreement with those previously reported in past years (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14), using different techniques and, the most often, restricted to the determination of the one or another of these proteins. Emergence of new analytical procedures in the late years, such as conventional or microparticleenhanced immunonephelometry, today allows major proteins of human milk to be analyzed with sensitivity, easiness, and singleness of methodologies.…”
Section: Discussionsupporting
confidence: 89%
“…There is some discrepancy between our results and other reports perhaps due to differences in the time of breast milk collection and studies not taking into account the degree of prematurity, parity and mode of delivery, variables that may significantly affect the bioactive protein levels. 3,11,15,25 In conclusion, transitional milk after term as well as preterm delivery is superior to mature milk in terms of the content of the bioactive proteins. Breast milk from mothers who deliver at less than 32 weeks of gestation is a good source of factors that have antibacterial and anti-inflammatory activities but is constantly deficient in leptin, which is involved in the regulation of the neuroendocrine system.…”
Section: Discussionmentioning
confidence: 97%
“…4,24 However, the data in the medical literature is inconsistent and some studies have shown no effect of nutrition and/or adiposity on the milk content of lactoferrin, lysozyme, sIgA and leptin. 25,26 We used a smaller sample of mothers who delivered at term but the data was collected consistently (four times) during the first month of lactation and found to be normally distributed. There is some discrepancy between our results and other reports perhaps due to differences in the time of breast milk collection and studies not taking into account the degree of prematurity, parity and mode of delivery, variables that may significantly affect the bioactive protein levels.…”
Section: Discussionmentioning
confidence: 99%